(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2022)
The decolonisation of education seems to require a clear understanding of the colonial education heritage in South Africa and an understanding of the emergent global trends that shaped policy and practice from the 19th century. This paper explores the origins of educational discourses and practices that emerged in England and formed the basis of colonial practices. It focuses on emergent policies aimed at educating the working classes in the industrial heartland, which came to influence the literate or scientific culture in the Cape during that time. It explores the hitherto neglected issue of the ideas and resources deployed in both contexts, with particular reference to printed materials that shaped that culture in the process of framing a secular and scientific culture in schools and popular culture of literacy amongst working-class people in the metropolis and African subject/citizens in the colonial context. It also traces gradual attempts to introduce a culture of literacy which embraced the African language and culture. These educational developments related to children’s schooling and the popular education of adults helped shape the state-controlled mass education system that emerged during the 20th century. This paper aims to begin an exploration of the complex dynamics of that process and open the way for further research on these neglected issues.